Status and weaknesses of epidemiological investigation and emergency response in Guizhou Province, China - Gou, Yun; Huang, Yan; Yu, Chun; Hu, Can; Tao, Zhongfa; Huang, Jiao; Deng, Bing; Lei, Mingyu (The Journal of Infection in Developing Countries, 2026)
Introduction: Epidemiological investigation and emergency response are crucial during public health emergencies. This work investigated the status and weaknesses of the Center for Disease Control and Prevention (CDC) system in Guizhou Province, China, before and after the coronavirus disease 2019 (COVID-19) pandemic to address the weaknesses of public health emergency preparedness. Methodology: This research was observational. It adopted a cross-sectional design, and designed two electronic questionnaires to collect data. One questionnaire was for 98 CDC agencies and the other was for 1026 individuals in Guizhou Province, China. The questionnaires focused on workforce, epidemiological investigation capacity, detection capacity, emergency material preparation, information technology application, and emergency response. Respondents completed electronic questionnaires via a WeChat application or by visiting a website link directly. Results: The workforce and detection capacity of CDC agencies have considerably increased. Among the factors influencing individual capacity, willingness to learn (OR = 4.649, 95% CI = 2.782, 7.767) was the most related to workers with strong capacity. Furthermore, weaknesses involving epidemiological investigation and emergency response were found in each CDC level. Conclusions: Remarkable improvements occurred during the COVID-19 pandemic in Guizhou Province, China. This study identified the weaknesses of epidemiological investigation and emergency response. It could provide decision-makers with directions for improvement, targeting each weakness at each CDC level to prepare for future disasters.